Variations in hepatic biomarkers in American alligators (Alligator mississippiensis) from three sites in Florida, USA. (July 2016) - Gunderson, Mark P.; Pickett, Melissa A.; Martin, Justin T.; Hulse, Elizabeth J.; Smith, Spenser S.; Smith, Levi A.; Campbell, Rachel M.; Lowers, Russell H.; Boggs, Ashley S.P.; Guillette, Louis J.
Abstract: Sub-individual biomarkers are sub-lethal biological responses commonly used in the assessment of wildlife exposure to environmental contaminants. In this study, we examined the activity of glutathione-s-transferase (GST) and lactate dehydrogenase (LDH), and metallothionein (MT) concentrations among captive-raised alligator hatchlings, wild-caught juveniles, and wild-caught adults. Juveniles and adults were collected from three locations in Florida (USA) with varying degrees of contamination (i.e. Lake Apopka (organochlorine polluted site), Merritt Island National Wildlife Refuge (NWR) (metal polluted site), and Lake Woodruff NWR (reference site)). We examined whether changes in the response of these three biomarkers were age and sex dependent or reflected site-specific variations of environmental contaminants. Juvenile alligators from Merritt Island NWR had higher MT concentrations and lower GST activity compared to those from the other two sites. This outcome was consistent with higher metal pollution at this location. Sexually dimorphic patterns of MT and GST (F > M) were observed in juvenile alligators from all sites, although this pattern was not observed in adults. GST activity was lower in captive-raised alligators from Lake Apopka and Merritt Island NWR as compared to animals from Lake Woodruff NWR, suggesting a possible developmental modulator at these sites. No clear patterns were observed in LDH activity. We concluded that GST and MT demonstrate age and sex specific patterns in the alligators inhabiting these study sites and that the observed variation among sites could be due to differences in contaminant exposure. Highlights: Site specific patterns in MT and GST were observed. Sexually dimorphic patterns of MT and GST were present in juvenile alligators. MT and GST patterns were consistent with metal exposure. Possible developmental modulation of GST could explain patterns. No clear patterns in LDH were present among sites or between sexes.